Diversité des agricultures familiales - Bosc, Pierre-Marie; Sourisseau, Jean-Michel; Bonnal, Philippe; Gasselin, Pierre; Valette, Elodie; Bélières, Jean-François (éditions Quae, 2014)
This book aims to explain the nature and the force of links between the family and the farm. It is constructed around twenty case studies in miscellaneous countries in Asia, Africa, Latin America and Europe. The authors clarify "